Inovasi Pengelolaan Sampah Berbasis Teknologi Waste To Energy Di Kota Malang (Studi Tempat Pembuangan Akhir Supiturang) - Amalia Rahmadani Anwar; Muhammad Kamil; Ach. Apriyanto Romadhan (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2020)
Increasing municipal waste is generated from every human activity. The purpose ofthe research is related to innovation in waste management using waste to energytechnology in the utilization of waste in the Supit Urang Landfill. Gas emissions fromlandfills that are piled up in landfills not only try to reduce and prevent humans, theenvironment and the earth from damage, but also the use of renewable energy.Descriptive qualitative research methods. Data collection techniques throughdocumentation, interviews and observation of field studies. Data analysis techniquesthrough the data collection of field study results (written or oral), examined, reduceduntil later drawn conclusions. Using Roger's innovation theory. The research resultsshow that the problem of waste is not only borne by the government. Wastemanagement must be completed from upstream to downstream from the communitysettlement to the final disposal site. The renewal of the management system in the useof waste has been in effect since the program decentralization from the Ministry ofPublic Works and Public Housing to the Department of Environment to build thelatest technology-based waste disposal system. German assistance in infrastructuredevelopment has been a factor in the success of the renewal of the Supit Urang landfillwaste utilization system. The output of the waste to energy program is electricity andgas. Increased energy production from landfills has benefited the community and alsolocal governments as energy producers.